Triggering of specific Toll-like receptors and proinflammatory cytokines breaks allergen-specific T-cell tolerance in human tonsils and peripheral blood - Kücüksezer, Umut Can; Palomares, Oscar; Rückert, Beate; Jartti, Tuomas; Puhakka, Tuomo; Nandy, Andreas; Gemicioğlu, Bilun; Fahrner, Heinz B.; Jung, Andreas; Deniz, Günnur; Akdis, Cezmi A.; Akdis, Mübeccel (Journal of allergy and clinical immunology, 2013)
The generation and maintenance of allergen-specific T-cell tolerance is a key step in healthy immune responses to allergens and successful allergen-specific immunotherapy. Breaking of peripheral T-cell tolerance to allergens can lead to the development of allergies, but the mechanisms are not completely understood. We sought to identify molecular mechanisms that break allergen-specific T-cell tolerance in human subjects. Proliferative responses of allergen-specific T cells from tonsils and peripheral blood were measured by using tritiated thymidine incorporation and carboxyfluorescein succinimidyl ester (CFSE) dilution experiments. Cytokine levels in cell-free supernatants were quantified by using the cytometric bead array, and mRNA expression of transcription factors and cytokines was determined by using quantitative PCR. Myeloid dendritic cells (DCs) were characterized by using flow cytometry. In allergic patients the immune profile of the tonsils represents the atopic status of patients, with low expression of the TH1 cell-specific transcription factor T-bet and the cytokine IFN-γ, as well as IL-10. Human tonsils show very low levels of allergen-induced T-cell proliferation, thus representing a very suitable in vivo model to assess mechanisms of breaking allergen-specific T-cell tolerance. Triggering of Toll-like receptor (TLR) 4 or TLR8 and the proinflammatory cytokines IL-1β or IL-6 break allergen-specific T-cell tolerance in human tonsils and peripheral blood through a mechanism dependent on the adaptor molecule myeloid differentiation primary response gene (88) (MyD88). In particular, myeloid DCs and stimulations that activate them broke the tolerance of allergen-specific CD4+ T cells, whereas plasmacytoid DCs and stimulations that activate them, such as TLR7 and TLR9, did not have any effect. Tolerance-breaking conditions induced by different molecular mechanisms were associated with a mixed cytokine profile with a tendency toward increased levels of IL-13 and IL-17, which are TH2 and TH17 cytokines, respectively. Certain innate immune response signals and proinflammatory cytokines break allergen-specific CD4+ T-cell tolerance in normally unresponsive subjects, which might lead to the development or exacerbation of allergic diseases after encountering microbes or inflammatory conditions.